Recent advances in surveillance colonoscopy for dysplasia in inflammatory bowel disease - Soo-Young Na; Won Moon (Korean Society of Gastrointestinal Endoscopy, 2022)
Inflammatory bowel disease (IBD) has a global presence with rapidly increasing incidence and prevalence. Patients with IBD including those with ulcerative colitis and Crohn's disease have a higher risk of developing colorectal cancer (CRC) compared to the general population. Risk factors for CRC in patients with IBD include long disease duration, extensive colitis, primary sclerosing cholangitis, family history of CRC, stricture, and prior dysplasia. Surveillance colonoscopy for CRC in patients with IBD should be tailored to individualized risk factors and requires careful monitoring every year to every five years. The current surveillance techniques are based on several guidelines. Chromoendoscopy with targeted biopsy is being recommended increasingly, and high-definition colonoscopy is gradually replacing standard-definition colonoscopy. However, it remains unclear whether chromoendoscopy, virtual chromoendoscopy, or white-light endoscopy has better efficiency when a high-definition scope is used. With the development of new endoscopic instruments and techniques, the paradigm of surveillance strategy has gradually changed. In this review, we discuss cutting-edge surveillance colonoscopy in patients with IBD including a review of literature.